Repressive autonomy: discourses on and surveillance of marriage migration from Turkey to Austria - Strasser, Sabine (Migration Letters, 2014)
Transnational marriages and family reunification have recently been assessed as one of the main obstacles to integration in Austria. They have been increasingly problematized and kept under surveillance when partners from third countries, in Austria particularly from Turkey, have been involved. Nonetheless, a great number of Turkish migrants and their descendants prefer to marry partners from their ‘country of origin’. In this paper I discuss practices of and discourses on family formation across borders based on an ethnographic fieldwork in a small town in Austria. Findings show that transnational marriages in Austria are often conflated with forced and fictitious marriages and consequently rejected as defraud or ‘violence in the name of tradition’. Furthermore, legal provisions against problematic marriages do not liberate women but repress their autonomy.